2018
DOI: 10.22159/ajpcr.2018.v11i3.22851
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Chives (Allium Schoenoprasum L.) Leaves Infuse as Inhibitor Calcium Lithogenesis on Urinary Tract

Abstract: Objective: This study examined the antilithogenesis activity by in vitro and histopathologic study from the infuse solution of chives leaves powder.Methods: The study begins with standard phytochemical screening on the powder of chives leaves. For performing in vitro antilithogenesis activity, atomic absorption spectrophotometry method was adopted to measure the dissolved calcium level. Histopathologic study was using animal models.Result: Phytochemical screening of chives leaves powder has a lot of phytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…About 300 g of the fine powder coriander leaf was extracted with 96% ethanol by using maceration for 5 days at room temperature.The ethanol extract of coriander leaf (EECL) solution part was evaporated by using rotary evaporator to get the crude extract. 6,7 Preliminary Phytochemical Screening The crude extract of EELC was screening by using the standard protocol to know the presence of phytochemical compounds. 8…”
Section: Extract Preparationmentioning
confidence: 99%
“…About 300 g of the fine powder coriander leaf was extracted with 96% ethanol by using maceration for 5 days at room temperature.The ethanol extract of coriander leaf (EECL) solution part was evaporated by using rotary evaporator to get the crude extract. 6,7 Preliminary Phytochemical Screening The crude extract of EELC was screening by using the standard protocol to know the presence of phytochemical compounds. 8…”
Section: Extract Preparationmentioning
confidence: 99%
“…Phytochemical screening carried out on M. cordata leaf fractions which are ethyl acetate, hexane, and water solvent includes examing the chemical secondary metabolites of alkaloids, flavonoids, glycosides, tannins, triterpenoids, and steroids [12][13][14][15].…”
Section: Preliminary Phytochemical Screening Of Extract and Fractionsmentioning
confidence: 99%
“…Previous studies have shown that infuse and extracts (ethanol and ethyl acetate) of chives leaves have anticalculi activity [4], [5], [6], [7]. Therefore, this study aims to examine the continuation of anticalculi effect using the ethyl acetate fraction of chives leaf to help the treatment of kidney stones by using traditional medicine.…”
Section: Introductionmentioning
confidence: 99%